2004
DOI: 10.1158/0008-5472.can-03-3881
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression, Amplification, and Androgen Regulation of TPD52 in Prostate Cancer

Abstract: Gains in the long arm of chromosome 8 (8q) are believed to be associated with poor outcome and the development of hormone-refractory prostate cancer. Based on a meta-analysis of gene expression microarray data from multiple prostate cancer studies (D. R. Rhodes et al., Cancer Res 2002;62:4427-33), a candidate oncogene, Tumor Protein D52 (TPD52), was identified in the 8q21 amplicon. TPD52 is a coiled-coil motif-bearing protein, potentially involved in vesicle trafficking. Both mRNA and protein levels of TPD52 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 63 publications
(73 reference statements)
5
118
0
Order By: Relevance
“…Tissue hybridization, washing, and fluorescence detection were performed as previously described. 29 The samples were analyzed under a  100 oil immersion objective using a Leica DM-RB fluorescence microscope equipped with appropriate filters. The corresponding H&E was available for side-byside comparison with the FISH section.…”
Section: Erg Gene Rearrangement Assessment By Fishmentioning
confidence: 99%
“…Tissue hybridization, washing, and fluorescence detection were performed as previously described. 29 The samples were analyzed under a  100 oil immersion objective using a Leica DM-RB fluorescence microscope equipped with appropriate filters. The corresponding H&E was available for side-byside comparison with the FISH section.…”
Section: Erg Gene Rearrangement Assessment By Fishmentioning
confidence: 99%
“…We crossed several studies from the recent literature based on microarray transcriptome analyses and ChIP-chip, ChIP-DSL or ChIP-paired end di-tag data obtained from mammary tumor cell lines (Lin et al, 2004(Lin et al, , 2007Laganiere et al, 2005;Kininis et al, 2007;Kwon et al, 2007) to select a group of relevant genes based on the following criteria: hormone-stimulated gene expression in ERa-positive mammary tumor cell lines, complete lack of expression in ERa-negative breast cancer cell lines (Nagaraja et al, 2006) and ERa target identified by ChIP. Thus, we investigated gene regulation of Annexin A9 (ANXA9), a gene coding for a protein of the annexin superfamily (Raynal and Pollard, 1994;Gerke and Moss, 2002), the RET proto-oncogene, which encodes a protein receptor tyrosine kinase with a zinc finger domain associated with dominantly inherited cancer syndromes (Goodfellow and Wells, 1995), the tumor protein D52-like 1 (TPD52L1 (D53)) upregulated in human breast and prostate cancers (Balleine et al, 2000;Ahram et al, 2002;Pollack et al, 2002;Rubin et al, 2004), bone morphogenetic protein-6 (BMP6), a multifunctional molecule of the transforming growth factor-b superfamily overexpressed in breast, prostate and salivary gland cancers (Hamdy et al, 1997;Heikinheimo et al, 1999) and the gene regulated in breast cancer 1 (GREB1), whose product contributes to the growthpromoting effects of estrogens in MCF-7 cells (Rae et al, 2005). We confirmed that expression of these genes was stimulated by estradiol in MCF7 cells (Figure 7a) and assessed changes in relative expression levels in the MDA-66 cells in the absence and in the presence of AZA.…”
Section: Dna Demethylation and Histone Deacetylation Trigger Hormone-mentioning
confidence: 99%
“…The first D52-like gene to be identified, human TPD52(hD52), was found to be overexpressed in f40% of breast carcinomas (2). Subsequent reports have shown that hD52 is overexpressed in cancers of the lung (8,9), prostate (3,10,11), colon (12), and ovary (13), as well as in B cell malignancies (14). The hD52 gene has been localized to human chromosome 8q21 (2), a region frequently gained in breast and prostate carcinomas (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%